Estimating stock market technical efficiency for truncated normal distribution: Evidence from Dhaka stock exchange - Hassan, Md Zobaer; Kamil, Anton Abdulbasah; Mustafa, Adli; Baten, Md Azizul (Academic Journal Inc, 2012)
This study analyzes the technical efficiency of selected groups of companies of Bangladesh Stock Market that is Dhaka Stock Exchange (DSE) market using a stochastic frontier production function.This research considers Cobb-Douglas Stochastic frontier model with truncated normal distribution and both the time-variant and time-invariant inefficiency effects are estimated.The studied input variables-market return, market capitalization, book to market ratio and market value show significant relationship with the stock returns.The estimated average technical efficiency of DSE market is 95.42% of potential output for the truncated normal distribution over the period 2000-2008.The results show that technical efficiency gradually decreases over the reference period.The value of technical efficiency is high for investment group and low for bank group in time-variant situation whereas the value of technical efficiency is high for investment group also but low for ceramic group in time-invariant situation.